Trauma Healing Pasca-Banjir: Penguatan Psikososial Siswa Sekolah Dasar di Desa Tambak Ukir, Situbondo - Ervia Toga; Achmad Efendi; Fransiska Erna Damayanti; Dian Roshanti (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Natural disasters, such as floods, frequently strike East Java, and particularly in Tambak Ukir Village, Situbondo, have a significant impact on the mental health of children, especially elementary school students. The trauma experienced from these disasters disrupts their psychosocial development, potentially hindering their learning processes and social interactions. This community service activity was conducted in the affected area in collaboration with the Student Disaster Preparedness Unit of Stikes Banyuwangi and Rumah Zakat Banyuwangi Volunteers, focusing on restoring the students' mental well-being. The method involved providing information and education, presented through games, to help them recover from the trauma of the disaster they experienced. The program aimed to increase the students' mental resilience, reduce trauma symptoms, and create a safer learning environment. Psychosocial support through trauma healing is crucial for recovery from traumatic experiences and building a better future. This community service project is expected to contribute to developing educational and mental health policies in disaster-prone areas. The implications of this project are significant, highlighting how structured psychosocial interventions can help children overcome disaster-related trauma. In conclusion, this trauma healing program represents a vital step in building the psychological resilience of children in post-disaster situations.